African beginnings. - Vlahos, Olivia; Ford, George, 1936- (New York, Viking Press, 1967)
A cultural history of Africa as determined by the work of archaeologists and anthropologists.
Bibliography: p. [267]-277.
Keywords: Ethnology -- Africa; Ethnology -- Africa; Africa -- History; Africa -- History; Africa -- Social life and customs